(untitled) (e-Journal of Linguistics, 2019)
Broca’s aphasic patients display language problems in initiating utterances with groping movements, multiple false attempts and self-correction resulting from a lesion to the third frontal convolution of the left hemisphere of the brain. This study describes the forms of sound impairment, types of errors and phonetic processing by a Balinese patient who suffered from non-fluent speech disorder. The results showed that KW’s speech performance was categorized severe. There were 0.80% phonological errors in word naming, 0.92% in picture naming, 0.87% in answering questions and 0.89% in oral reading. Of the three other types of errors, sound substitution errors mostly appeared in every phonological task. He made 65% sound substitutions, 20% sound distortions, 10% sound insertions and 5% omissions. Different speech stimulation could trigger sound inconsistency. The phonological errors occurred because there was not any appropriate coordination between phonological representation and phonetic realization due to the loss of linguistic message in Broca’s area.